The Embedded Market and Ideology Critique - Johnson, Pauline (Critical Horizons, 2011)
The article examines the ideology critical potentials of the concept of the embedded market, made famous by philosopher and economic historian Karl Polanyi. It explores several readings of this concept and assesses their ability to revive critical powers of sociology. It discusses the book "The New Spirit of Capitalism," by Luc Boltanski and Eve Chiapello, as a specific take on such an idea. It also offers a re-examination of Polanyi's interpretations of the embedded markets thesis.
Sociology; Philosophy
Keywords: Boltanski and Chiapello; embedded markets; ideology; neoliberalism; philosophers; philosophy; social theory; sociology

The second great transformation: Towards a solidarity society - Brie, Michael; Klein, Dieter (International Critical Thought, 2011)
The double transition to a society based on unfettered capital valorisation, which attempts to legitimize itself by claiming to be a democratic society founded on human rights, can be defined as the first great transformation of the contemporary period. These bourgeois capitalist societies are now in a crisis of their reproduction, integration, rule and security. Three possible scenarios can be discerned: the first attempts to continue the present development (conventional world), the second, the formation of authoritarian fortresses in the centres within an ocean of insecurity and degradation, or, the third, a new transformation to a solidaristic social development. This transformation would begin in capitalism and at the same time point beyond it to a society whose most important goal is the development of free individuals through solidarity-based associations in the economy, in politics and in culture. Its basis would be a solidarity-based multi-sector economy and a participatory democracy. Although the totality of a new society cannot be anticipated, concrete entry projects for a new second transformation can be developed.
Philosophy; Political Science
Keywords: capitalism; double transformation; socialism; solidarity economy

Marketization, social protection and emancipation: ambivalences of feminism in the capitalist crisis - Fraser, Nancy (Revista Direito GV, 2011)
This article is a reflection on the perspectives of feminism in the context of the current crisis of neoliberal capitalism. It is based on the theories of Karl Polanyi that explained the historical process of the crises as a result of the conflict between two elements – marketization and social protection. However, Polanyi Kept out of sight forms of injustice that are not present in the market. He also had the tendency to excuse the social protection as an instrument of domination. This article takes a broader view on the analysis of the conflict between Marketization and social protection. It includes in the analysis a third dimension, the emancipation. The inclusion of this third element transforms the historical process in a three dimensional conflict and forms the heart of a quasi-polanyian perspective that is able to explain the crisis of the XXI century. This text develops this new perspective and uses it to analyze the bets in the emancipation of the gender hierarchy. The triple movement, thus constituted, can overcome the ambivalence of feminism, as the feminist agenda was often manipulated by neoliberalism. The redefinition of social protection in democratic, participatory, non-hierarchic and non-oppressive terms, opens the possibility to a new feminist politics. Keywords: Capitalism; Emancipation; Welfare State; Feminism; Gender.
Philosophy; Political Science
Keywords: capitalism; emancipation; feminism; gender; welfare state

Marketization, Social Protection, Emancipation: Toward a Neo-Polanyian Conception of Capitalist Crisis - Fraser, Nancy (Business as Usual: The Roots of the Global Financial Meltdown, 2011)
BOOK ABSTRACT: Situates the current crisis in the historical trajectory of the capitalist world-system, showing how the crisis was made possible not only by neoliberal financial reforms but by a massive turn away from manufacturing things of value towards seeking profit from financial exchange and credit. Much more basic than the result of a few financial traders cheating the system, this is a potential historical turning point. In original essays, the contributors establish why the system was ripe for crisis of the past, and yet why this meltdown was different. The volume concludes by asking whether as deep as the crisis is, it may contain seeds of a new global economy, what role the US will play, and whether China or other countries will rise to global leadership. Contributors include: Giovanni Arrighi, Gopal Balakrishnan, Manuel Castells, Daniel Chirot, Fernando Coronil, Nancy Fraser, James K. Galbraith, David Harvey, Caglar Keyder, Beverly J. Silver, and Immanuel Wallerstein. The three volumes can purchased individually or as a set. Business as Usual is the first part of a trilogy comprised of the first three books in the Possible Future series. Volume 1: Business as UsualVolume 2: The Deepening CrisisVolume 3: Aftermath The three volumes are linked by a common introduction and can be purchased individually or as a set.
Philosophy; Political Science
Keywords: capitalism; emancipation; feminism; gender; welfare state

Y a-t-il une économie sartrienne ? - Kail, Michel; Sobel, Richard (L'Homme & la société, 2011)
RésuméEn dépit de l’absence d’un exposé économique systématique dans l’œuvre de Sartre, nous soutenons qu’il y a bien une économie sartrienne, même si celle-ci est encore à développer. Le statut que Sartre réserve à la « rareté » lui permet de faire un pas supplémentaire vers la critique de l’économisme par rapport à celui déjà effectué par Karl Polanyi, qui s’est contenté de récuser la confusion entretenue entre l’économique et sa définition formelle. La rareté, nous enseigne Sartre, ne saurait en effet être soumise au traitement de la raison instrumentale, mais considérée, ajoute-t-il, comme un fait humain dans l’histoire. Aussi, l’analyse économique ne doit-elle pas s’appuyer sur la notion de « nature » et la thématique de l’homme confronté à la nature, en l’occurrence « ingrate », mais articulée sur la notion de « monde » telle que la philosophie sartrienne l’élabore., Despite the absence of a systematic analysis of economics in Sartre’s work, we argue that there can indeed be said to be a Sartrean economics, even if it is one that still awaits development. The status which Sartre accords to the concept of Scarcity allows him to advance the critique of economism begun by Karl Polanyi, who, for his part, had been satisfied simply to challenge the reduction of economics to its formal definition. Scarcity, Sartre teaches us, should not be submitted to the process of instrumental reason, but considered as a fact of human history. Economic analysis, meanwhile, should not be based solely on the theme of man’s confrontation with a typically ungrateful Nature, but articulated through the concept of World as elaborated in Sartrean philosophy.
Political Science; Philosophy
Keywords: SARTRE; Jean-Paul; 1905-1980; economic systems